Impact of a structured social and emotional learning curriculum on academic achievement among middle school students in UAE - Jarrah, Hani Yousef; Nser, Khald Khamis; Alhrahsheh, Rakan; Alkhasawneh, Tareq; Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2024)
This study aims to analyze the impact of a structured Social and Emotional Learning (SEL) curriculum on the academic performance of middle school students in the United Arab Emirates (UAE). Using a randomized control group design, a total of three hundred students took part in the study. The results showed a statistically significant improvement in academic achievement among those who were exposed to the SEL intervention. Correlation studies examined a positive relationship between college students' involvement in the SEL program and improved academic achievement. The innovative contribution of the study is in its examination of the intricate relationship between SEL involvement and academic achievement, particularly within the unique educational system of the UAE. The findings emphasize the practical and philosophical significance of integrating Social and Emotional Learning (SEL) into Middle School teaching to enhance cognitive and socio-emotional development.